Pemenuhan Hak Muammar Khadafi Sebagai Hors de Combat dalam Konflik Bersenjata Libya - Rintario Adhi Kameswara; Sri Lestari Rahayu (Faculty of Law Universitas Sebelas Maret, 2019)
This article describes and examines the problem of how to fulfill hors de combat rights in armed conflict with the case study of Muammar Khadafi’s human rights violations as hors de combat. Methodology and research used are normative research methods that have the same definition as doctrinal research, namely research based on legal materials whose focus is on reading and studying primary and secondary legal materials. Based on the results of the study, the authors concluded that the rights of Muammar Gaddafi as Hors de Combat were not fulfilled in accordance with International Humanitarian Law. This is because it violates the provisions contained in the Geneva Conventions of 1949 concerning the treatment of sick and injured combatants, and Additional Protocol I 1977 because in this case Muammar Khadafi is a person who has legitimate hors de combat status.